EVALUATING GENERATIVE ARTIFICIAL INTELLIGENCE AND INTERNET SEARCHES IN FOREIGN LANGUAGE GRAMMAR LEARNING: EXAMINING THE ROLE OF EXPERTS THROUGH A STUDY ON VOCABULARY BEGINNING WITH “MER-” IN MALAY - Murata, Yumie (Journal of Research and Innovation In Open and Distance Learning, 2023)
This study aimed to clarify the usefulness and limitations of generative artificial intelligence (AI) and online information in the self-study of foreign languages, and to reassess the domain of roles that humans, such as language teachers and experts, should perform. As a learner of Malay, the author attempted to pursue this objective by seeking solutions to grammar-related questions that arose during the process of learning Malay without directly asking teachers or specialists, instead posing questions to generative AI or conducting Internet searches. The author first pursued the question of using the form "mer-" as a prefix-like element in Malay. The author attempted to resolve this question by applying it to generative AI, including ChatGPT, and by conducting an Internet search. It transpired that the generative AI could not distinguish between prefixes and other elements, and thus failed to resolve the question. Next, through an Internet search and reviewing literature, although no discussions on "mer-" were found in Japan, the following three positions regarding "mer-" were observed in Malaysia: (1) the prefix "mer-" does not exist at all, (2) "mer-" used to be a prefix in the past but was no longer considered as such, and (3) it should be "mar-" instead of "mer-." However, it was not possible to obtain information on whether there possibly were other positions, or if one of these positions had been conclusively proven to be correct. Translations by ChatGPT proved to be useful for understanding literature written in Malay. Internet searches were effective in identifying the relevant literature, even with small search terms. Language teachers and experts are needed for answering to learner’s grammar-related questions. They would also contribute to the development of specialized AI capable of answering grammar-related questions, enabling AI to fulfill this role for learners in the future. Language teachers and experts can then focus on researching other unresolved issues.